Dupilumab provides important clinical benefits to patients with atopic dermatitis who do not achieve clear or almost clear skin according to the Investigator's Global Assessment: a pooled analysis of data from two phase III trials. (11th April 2019) - Silverberg, J.I.; Simpson, E.L.; Ardeleanu, M.; Thaçi, D.; Barbarot, S.; Bagel, J.; Chen, Z.; Eckert, L.; Chao, J.; Korotzer, A.; Rizova, E.; Rossi, A.B.; et al.
Summary: Background: In the U.S.A., an Investigator's Global Assessment (IGA) score of ≤ 1 (clear or almost clear skin) has been the standard measure in regulatory outcomes for registration clinical trials in atopic dermatitis (AD), including those supporting the recent approval of dupilumab. Objectives: To evaluate the treatment effect of dupilumab in patients with IGA > 1 at the end of treatment, using other validated outcome measures for AD signs, symptoms and quality of life. Methods: LIBERTY AD SOLO 1 and 2 were two 16‐week, randomized, double‐blind trials enrolling adult patients with moderate‐to‐severe AD (IGA ≥ 3) inadequately controlled with topical treatment. We performed a post hoc analysis in patients receiving dupilumab 300 mg every 2 weeks (q2w) or placebo. Outcome measures in patients with IGA > 1 included Eczema Area and Severity Index (EASI), pruritus numerical rating scale (NRS), affected body surface area (BSA), Patient‐Oriented Eczema Measure (POEM) and Dermatology Life Quality Index (DLQI). The trials were registered at ClinicalTrials.gov: NCT02277743 and NCT02277769. Results: At week 16, 278 of 449 dupilumab q2w‐treated patients (median age 36·0 years) and 396 of 443 placebo‐treated patients had IGA > 1. Among patients with IGA > 1 at week 16, dupilumab significantly improved several outcome measures compared with placebo: EASI (−48·9% vs. −11·3%, P < 0·001), pruritus NRS (−35·2% vs. −9·1%, P < 0·001), affected BSA (−23·1% vs. −4·5%, P < 0·001), POEM score ≥ 4‐point improvement (57·4% vs. 21·0%, P < 0·001) and DLQI score ≥ 4‐point improvement (59·3% vs. 24·4%, P < 0·001). Conclusions: In patients with IGA > 1 at week 16, dupilumab induced statistically significant benefits in multiple validated outcome measures compared with placebo. The IGA ≤ 1 end point significantly underestimates clinically relevant dupilumab treatment effects. Abstract : What's already known about this topic? An Investigator's Global Assessment (IGA) score of 0 or 1 (clear or almost clear skin) is considered the regulatory standard for treatment success in trials of patients with atopic dermatitis in the U.S.A. It is currently unknown whether patients receiving dupilumab treatment for moderate‐to‐severe atopic dermatitis derive clinical and quality‐of‐life benefit even if they have an end‐of‐treatment IGA score > 1. What's does this study add? This post hoc analysis of patients with an end‐of‐treatment IGA score > 1 from two randomized, placebo‐controlled trials showed that after 16 weeks of treatment dupilumab significantly improved their outcome measures compared with placebo, including measures of signs, symptoms and quality of life. These results show that the regulatory IGA ≤ 1 end point used in clinical trials significantly underestimates clinically relevant dupilumab treatment effects, underscoring potential limitations of the IGA scale. Linked Comment: de Bruin‐Weller. Br J Dermatol 2019; 181 :12–13 . Respond to this article